Kaolinite Nanotubes as Support Catalysts of Sulfuric Acid (H2SO4) for Transesterification Reaction of Waste Cooking Oil into Methyl Ester for Biodiesel - Fitri, Ernarisa; Rahadian Zainul; Syukri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
This study aims to improve the catalytic performance of kaolinite by converting it into kaolinite nanotubes and utilizing it as a support for sulfuric acid catalysts. Analysis using XRD and TEM revealed that the kaolinite crystal phase remained stable after being modified with sulfuric acid, while kaolinite nanotubes underwent little structural change. In addition, characterization via FTIR and XRF confirmed the presence of sulfate ions in kaolinite nanotubes and kaolinite after combination with sulfuric acid. Catalytic test on transesterification of used cooking oil under uniform conditions (catalyst 3% w/v, oil to methanol ratio 1:6, temperature 90 Â°C, and stirring speed 700 rpm) showed that sulfuric acid supported by kaolinite nanotubes gave the best performance, producing methyl ester of 65.01%. These findings indicate that converting kaolinite into nanotubes significantly improves its performance as a catalyst support. Practically, this increase in catalytic activity contributes to the efficiency of used cooking oil-based biodiesel production, which can reduce dependence on virgin vegetable oil raw materials and support waste oil recycling efforts. In addition, the use of cheap and easily available kaolinite-based catalysts can reduce the cost of biodiesel production, making it more competitive as an environmentally friendly fuel.